PENGARUH PEMBAYARAN DIVIDEN TUNAI, PELUANG INVESTASI DAN UKURAN PERUSAHAAN TERHADAP ABNORMAL RETURN PADA SEKTOR MANUFAKTUR DI BURSA EFEK INDONESIA - Isnurhadi .; Billy Ramadha; Marlina Widiyanti (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
This study aim to discuss the impact of dividend announcement to changes in stock prices on the manufacturing sector Indonesia Stock Exchange for 2011-2015 period. Event study used in the first section to examine abnormal retrun around cash dividend announcement date. Meanwhile panel regression used to examine the impact of cash dividend payment, investment opportunity and firm size to cummulative abnormal return. The data used was the financial report ofÂ  manufacturing sector firm for 2011-2015 period that pay cash dividend 5 years consecuitvely. The result show that there was significant abnormal return after the announcement. Meanwhile on the second section the result show that partially cash dividend payment has significant impact to cummulative abnormal return. The implication of this study was there were found positive cummulative abnormal return around dividend announcement date which is caused significantly by dividend yield thus prove the bird in hand theory